Atomic Force Microscopy (AFM) nanomechanical characterization of micro- and nanoplastics to support environmental investigations in groundwater - Massimiliano Galluzzi; Michele Lancia; Chunmiao Zheng; Viviana Re; Valter Castelvetro; Shifeng Guo; Stefano Viaroli (Emerging Contaminants)
Micro and nanoplastic (MNP) pollution is a severe environmental issue, posing potential risks to environmental and human health due to the intrinsic toxicity of plastic particles and their capacity to adsorb other pollutants. The diffusion of plastic debris affects all the environmental domains, including groundwater which was erroneously believed to be protected by the porous structure of the soil. Advanced spectroscopic techniques can detect the polymer type and quantify the number of MNP particles but are affected by large uncertainties in case of particles smaller than 10 μm in size and MNP heteroaggregates. To advance in the morphological and mechanical characterization of MNPs, a new protocol based on multifrequency Atomic Force Microscopy (AFM) is proposed with the support of the custom open software “MultiFreq AFMSuite”. Reconstituted MNP samples in pristine and aged conditions are used to fine-tune the methodology. Multifrequency AFM allows the detection of MNPs up to the nanometric scale based on elastic modulus assessments. The proposed technique also provides an in-depth analysis of the MNP surface roughness and the morphological characterization of particle aggregates. MNP particles from groundwater samples result in aggregates with a roughness of one to two orders of magnitude higher than the plastic particles aged in the laboratory, suggesting a higher adsorption capacity towards pollutants or other natural compounds. The application of the proposed method can facilitate the characterization of micro-and nanoplastics in groundwater, a resource characterized by large uncertainties in hydrodynamics and pollutant transport.